The Many Martins of Venantius Fortunatus. Venantius Fortunatus’ Martin-Poems as Instances of Individual Appropriation and Literary Offers of Ritual-Like Experience - Friedrich, Enno; Gärtner, Ursula (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The aims of this article are  to show the variety of characterizations of Saint Martin in the poetic texts by Venantius Fortunatus, mainly his Carmina, to explain this variety from the historical contexts of different poems, and  to describe the effect that it might have had on the readers of the collection of poems in the interplay between literature and ritual. Saint Martin is characterized in a wide array of ways in Fortunatus’ occasional poems, which does not provide a congruent picture of the saint, but seems to serve the needs of particular audiences, who are presented with a version of Saint Martin tailor-made for them. The readers of the Carmina as a unified collection of many such poems are forced to reconcile the different characterizations with each other and with their own expectations about the saint. As they do so, they can have an experience similar to the social experience of members of a congregation in the cult of Saint Martin.
Keywords: aesthetics of reception; Carmina; cult of the saints; Individual appropriation; resonance; Saint Martin; Venantius Fortunatus